Improving optical coherence tomography theories and techniques for advanced performance and reduced cost - Wang, Nanshuo (2019)
Optical coherence tomography (OCT) has been developed as a high-resolution three-dimensional imaging technique for clinical diagnosis. This thesis proposes several theoretical discoveries and technical improvements to the current OCT systems aiming to drastically reduce system costs while achieving the state-of-the-art performance.